2022
DOI: 10.5817/cp2022-4-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotion background on pathological internet users’ comments on online news: Evidence from online text analysis

Abstract: The increased use of Internet communication emphasizes the need to explore the characteristics of online comments, which help better understand their impact on individuals’ internal emotional states and how the emotional valence of online news impacts online commentaries among Pathological Internet Users (PIUs). Eighteen PIUs and 14 controls commented on online news of two types (positive and negative valence) under two separate elicited emotional states (positive and negative), with commentaries analyzed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previously, Jiang et al showed that the use of perceptual words and health-related vocabulary in patients' texts in online health community can have an impact on the social support they receive [27]. Similar studies have shown that how words are used in textual representations is also important [28,29]. Therefore, this study takes into full consideration the characteristics of physician online communities and innovatively introduces several words commonly used in the medical field into post analysis.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Previously, Jiang et al showed that the use of perceptual words and health-related vocabulary in patients' texts in online health community can have an impact on the social support they receive [27]. Similar studies have shown that how words are used in textual representations is also important [28,29]. Therefore, this study takes into full consideration the characteristics of physician online communities and innovatively introduces several words commonly used in the medical field into post analysis.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The score of each item ranged from 1 to 5 (1 = strongly disagree, 5 = strongly agree) and a higher score shows a higher level of Internet addiction (α = 0.94). This scale has been widely used to assess participants' Internet addiction in China, such as studies by Leng et al [ 56 ] or Zhang et al [ 57 ], and the reliability (α = 0.90) and validity (χ 2 (169) = 570.132, χ 2 / df = 3.374, CFI = 0.940, RMSEA = 0.070, SRMR = 0.057) of the scale in the current study were also good.…”
Section: Methodsmentioning
confidence: 99%